Biomechanical Comparison of External Fixation and Double Plating for Stabilization of a Canine Cadaveric Supracondylar Humeral Fracture Gap Model - Castaldo, Sarah; Syrcle, Jason; Elder, Steve; Wills, Robert W. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective Successful stabilization of comminuted supracondylar humeral fractures is challenging, and biomechanical studies are scarce. This study compares double-plate (DB-PLATE) and linear external fixator with an intramedullary pin tie-in (ESF-IMP) fixation techniques in a cadaveric gap model. The hypothesis was the DB-PLATE construct would be stiffer, stronger and more resistant to repeated loading than the ESF-IMP construct in both cyclic and load-to-failure axial compression testing.Study Design A 2 cm ostectomy was performed on 10 pairs of canine cadaveric humeri proximal to the supratrochlear foramen. Stabilization was with DB-PLATE (n = 10) or ESF-IMP (n = 10). Cyclic testing was performed by applying a 200 N load at 2 Hz for 63,000 cycles. Axial compressive load to failure testing followed. Data analysed included dynamic stiffness, stiffness and yield load.Results No constructs failed during cyclic testing or lost stiffness over time. Mean dynamic stiffness over the final 100 cycles was greater for DB-PLATE compared with ESF-IMP. Mean stiffness of DB-PLATE in load-to-failure testing was not different than ESF-IMP. Yield load of DB-PLATE was higher than ESF-IMP.Conclusion Both DB-PLATE and ESF-IMP survived cyclic testing with no change in dynamic stiffness. DB-PLATE was stronger than ESF-IMP in load-to-failure testing, which may make this construct preferable when prolonged healing or poor patient compliance is anticipated. Results suggest that either method may be appropriate for fixation of comminuted supracondylar humeral fractures.
Keywords: supracondylar; humerus; external fixator; biomechanical testing; double-plate fixation